Analisis Sejarah, Dampak, Dan Penanggulangan Bencana Gempa Bumi Pada Saat Pandemi Covid-19 Di Sulawesi Barat - Dedy Hartono; Rio Khoirudin Apriyadi; Tri Winugroho; Aprilyanto Aprilyanto; Siswo Hadi Sumantri; Wilopo Wilopo; Hafizh Surya Islami (PendIPA Journal of Science Education, 2021)
[Analysis of the History, Impact and Management of Earthquake Disaster during the Covid-19 Pandemic in West Sulawesi] Geographical, demographic, sociological, meteorological and climatological conditions of Indonesia make Indonesia in a disaster-prone area (natural, non-natural, and social). This condition can be used as a laboratory to produce disaster experts, knowledge and technology in Indonesia. Law 24/2007 as a framework for disaster management systems in Indonesia currently prioritizes the disaster mitigation paradigm so that a strong commitment and participation of all parties is needed to build and run this system properly. However, currently Indonesia is faced with multiple disasters that occurred during the Covid-19 pandemic. This is supported by data on the earthquake disaster in West Sulawesi on January 15, 2021 which occurred amid the potential for the spread of Covid-19 infection. The character of the risk in this problem is how to minimize the time for evacuation, emergency response and recovery of community conditions without neglecting the potential for transmission of Covid-19 infection. This study uses a descriptive quantitative approach with secondary data in the form of BNPB volunteer desks, BNPB current situation reports and population data and civil records. The data analysis technique uses quantitative methods through univariate analysis. The results showed that the history of disaster recorded that in West Sulawesi, there had been an M ? 6 RS earthquake in 1820, 1976, 1969, 1984 and 2021. The earthquake of January 15, 2021 occurred at 01.28.17 WIB with a magnitude of M 6.2 RS at depth of 10 km with the location: 2.98 LS, 118.94 BT (6 km northeast of Majene). The potential affected population in Majene Regency is 59,543 people, Mamasa Regency 62,007 people, Mamuju Regency 144,377 people, Polewali Mandar Regency 219,305 people. Quick response was shown by Indonesia through the President's direction to BNPB, Ministry of Social Affairs, Basarnas, TNI and Kapolri and their staff to take emergency response steps as soon as possible through Emergency Response Status No.001 / Darurat-SB / I / 2021 which is valid for 14 days (15-28 January 2021). The seventh main sectors in the emergency response are search and rescue, logistics or soup kitchens, shelters, mapping, clean water, sanitation and hygiene, communication and health.